2005
DOI: 10.2337/diacare.28.8.1869
|View full text |Cite
|
Sign up to set email alerts
|

Foot Ulcer Risk Is Lower in South-Asian and African-Caribbean Compared With European Diabetic Patients in the U.K.

Abstract: OBJECTIVE—To determine 1) foot ulcer rates for European, South-Asian, and African-Caribbean diabetic patients in the U.K and 2) the contribution of neuropathy and peripheral arterial disease (PAD) differences to altered ulcer risk between the groups. RESEARCH DESIGN AND METHODS—In this U.K. population–based study, we screened 15,692 type 1 and type 2 diabetic patients in the community health care setting for foot ulcers, foot deformities, neuropathy, and PAD plus other characteristics. In total,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
110
6
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(132 citation statements)
references
References 49 publications
6
110
6
10
Order By: Relevance
“…to patients with moderate to severe neuropathy. Indeed, in previous studies from our group we reported that 43% of a clinic-based diabetes cohort had VPT >25 [36], and 44% of a community cohort had NDS >3 [37], suggesting that these results apply to a substantial proportion of patients with diabetes.…”
Section: Discussionmentioning
confidence: 51%
“…to patients with moderate to severe neuropathy. Indeed, in previous studies from our group we reported that 43% of a clinic-based diabetes cohort had VPT >25 [36], and 44% of a community cohort had NDS >3 [37], suggesting that these results apply to a substantial proportion of patients with diabetes.…”
Section: Discussionmentioning
confidence: 51%
“…We were able to conduct several sensitivity analyses and found that our inability to determine race/ethnicity was not likely to have influenced our measurement of eGFR. Further, Abbott et al (22) did note various rates of foot complications and PAD and DFU in ethnic groups. However, these authors concluded that variable rates of PAD and neuropathy at least partially explained the different rates of LEA and DFU in these ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…In Western countries, foot ulcers are more common in male patients [22], and in mixed populations, foot ulceration is more common among those of European origin when compared to Asians and African-Caribbeans [31]. However, the greatest single risk factor for foot ulceration is a past history of either ulceration or amputation [6].…”
Section: Pathogenesis Of Diabetic Foot Ulcerationmentioning
confidence: 99%